ANALISIS PERLAKUAN AKUNTANSI UNTUK KREDIT BERMASALAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK CABANG MANADO - Tumbel, Deisy M.; Kalangi, Lintje; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2018)
Non-performing Loans in generally are loans that pay for their mortgage payments and/or Â the interest has passed 90 days or the due date, or loans whose payments are timely are in doubt. Non-performing Loans consist of loans sich as substandartd, doubtfull, loss. The research method used is descriptive method, namely data collected, analyzed, and compared then drawn to conclusion. The result of the study obtained showed that the accounting treatment of non-performing loans at PT. Bank Rakyat Indonesia (persero) Tbk Manado Branch, is in accordance with SFAS No. 50, 55 and 60 concerning to the presentation, recognition, measurement and disclosure. Keywords: Non-performing Loans, Accounting Treatment